Pengaruh Harga, Digital Marketing dan Lokasi Terhadap Keputusan Pembelian di Café Coffee Cirenggot - Cucu Hodijah; Mariati Tirta Wiyata; Zeffanya Raphael Wijaya (Cakrawala Repositori IMWI, 2023)
This study aims to determine the effect of price, digital marketing and location on purchasing decisions at Café Coffee Cirenggot. This study uses a type of quantitative research with accidental sampling technique of 80 respondents. The instrument test used is validity and reliability test, and multiple regression analysis in the form of hypothesis testing and F test and coefficient of determination (R2) analysis. Results: Based on the results of data analysis or hypothesis testing in this study, it shows that Digital Marketing has a significant effect on purchasing decisions, while Price and Location are rejected because they have no significant effect on Purchasing Decisions at Café Coffe Cirenggot.